Volcanic and epiclastic sucessions of Punta Atahuanca (Huacho, north of Lima) - Jara, Rosa (2011)
Albiano volcanic and volcano-sedimentary successions are exposed on the coastal cliffs such as those found north of the city of Huacho (Punta Atahuanca). In these successions, intercalations of volcanic levels of cushion lava, epiclastic levels and volcano-sedimentary levels can be observed, which are affected by a main fault system, showing a slight tilting on the west side. The presence of slumps at some levels of the sequence, is evidence of the activity generated in the basin formation process. The volcanic succession is interrupted at the top by a discordance on which a conglomeratic succession that corresponds to an alluvial fluvian fan lies horizontally.